Respiratory effects of exposure to flour dust: A case study among workers of flour production factories in Arak - Rafiee-Pour, Atena; Rafiee-Pour, Elnaz; Asghari, Mehdi; Gholam Zadeh, Narges; Farhang Dehghan, Somayeh (Archives of Advances in Biosciences, 2015)
Flour dust has been introduced as one of the effective factors in the prevalence of respiratory disorders among the workers of the flour production factories. The purpose of the present study is to examine the effects of this pollutant on the pulmonary functions and survey the prevalence of respiratory symptoms among workers of flour production factories in Arak, Iran. Exposure to flour dust is used to classify subjects into exposed (38 male workers of production plant) or unexposed groups (37 male employee from administrative section). Exposure level to flour dust, the prevalence of respiratory symptoms and pulmonary function in two group were studied using air sampling (based on method NIOSH 0600), a researcher made questionnaire on respiratory symptoms and Spirometer, respectively. The results indicated that workers of the production plant are exposed to high concentration of flour, which causes a decrease in the ratio of FEV1 / FVC compared to the unexposed ones. Among study respiratory symptoms, subjects had reported significantly more sputum secretion than that in control group. Furthermore intervening parameters, including age, work experience, body mass index and smoking didn’t show a significant effect on the pulmonary function of the individuals. Exposure to flour dust concentration with higher than threshold level values causes a decrease in workers respiratory capacity. Therefore, it is recommended that the reduction of both exposure risk and the 8-hour time-weighted average concentration of flour dust should be considered.